The Neuroimmunology of Multiple Sclerosis: Fictions and Facts - Pachner, Andrew R. (Frontiers in Neurology, 2022)
There have been tremendous advances in the neuroimmunology of multiple sclerosis over the past five decades, which have led to improved diagnosis and therapy in the clinic. However, further advances must take into account an understanding of some of the complex issues in the field, particularly an appreciation of “facts” and “fiction.” Not surprisingly given the incredible complexity of both the nervous and immune systems, our understanding of the basic biology of the disease is very incomplete. This lack of understanding has led to many controversies in the field. This review identifies some of these controversies and facts/fictions with relation to the basic neuroimmunology of the disease (cells and molecules), and important clinical issues. Fortunately, the field is in a healthy transition from excessive reliance on animal models to a broader understanding of the disease in humans, which will likely lead to many improved treatments especially of the neurodegeneration in multiple sclerosis (MS).